The Participation Management of Administrators Affecting to Teachers’ Performance Motivation at The Schools in Phranakhon Sri Ayutthaya Primary Education Area 1 - Siwilai, Suphirat; Techawattanasiridumrong, Wacharapatr (Mahachula Academic Journal, 2021)
This research aimed to (1) to study the participatory administration of the school administrators (2) to study the motivation of the teachers’ performance. The research population was 2,678 teachers under the Ayutthaya Primary Educational Service Area Office 1. 366 teachers under the Ayutthaya Primary Educational Service Area Office 1, specifying the sample size using the Crazy and Morgan tables. And divide the sample according to the proportion of the population With stratified randomness The research instruments were 1 research questionnaire for teachers. The confidence value was 0.93. The statistics used in the research were frequency, percentage, mean and standard deviation. The results of the research showed that (1) the participatory administration of the administrators under the Ayutthaya Primary Educational Service Area Office 1, in general, had a high level of action ( = 4.41). Found that the action factor level The side with the highest mean values ​​is Trust Was at the highest level ( = 4.76), followed by the independence of the work responsibility. Was at the high level ( = 4.49) and the side with the lowest mean was Commitment ( = 4.08) (2) The motivation for the performance of school teachers under the Ayutthaya Primary Educational Service Area Office, District 1, overall had the motivation level. Was at a high level ( = 4.50). When considering each side, it was found that the motivation level The side with the highest mean values ​​is The need for praise is accepted. At the highest level ( = 4.90), followed by the need for success in life. Is at the highest level ( = 4. 58) and the side with the least mean value was Aspects of security and safety requirements Very high level ( = 4.06).